PERLINDUNGAN HUKUM BAGI PENYEDIA ATAS PENGHENTIAN KONTRAK PENGADAAN BARANG DAN JASA - DIMAS TEGAR PALILING (Lembaga Penelitian dan Pengabdian Masyarakat, 2017)
From the juridical standpoint that there are issues that are not acomodate in the technical regulations for the procurement of goods and services, in this presidential regulation Number 54 year 2010 along with the revised document. In an implementation of the contract for the procurement of goods and services, such as the implementation of the construction made possible the occurrence state of kahar. the goal of the research in this paper is analyzing the meaning of termination of contracts in the procurement of goods and services and analyze the legal consequences of termination of the contract against the execution of a contract for the procurement of goods and services .Research methods used in the writing of scientific papers using normative legal research methods. Research results show that the meaning of termination and termination of Contracts for the procurement of goods and services differs. Termination of the contract is a contract that is caused by the suspension not work power force of the implementation of the contract, but the contract still exist, such as the circumstances of the termination of legal consequences whereas kahar contract is the Provider is entitled to payment for the work that has been done and the user must make payment upon receipt of the goods/services; and the provider is entitled to financial compensation, in unison with the user having to provide financial compensation for the delay in payment, include the clause of the contract to change the determination of the length of time until when the contract is terminated and payout system.